SPECIAL AND INCLUSIVE EDUCATION IN RURAL EDUCATION: THE INFRASTRUCTURE FOR SPECIALIZED EDUCATIONAL SERVICES IN RURAL SCHOOLS - Santos da Silva Júnior, João (Revista Gênero e Interdisciplinaridade, 2025)
Goal 4 of the National Education Plan (PNE) 2014-2024 aimed to universalize access to basic education for students targeted by Special and Inclusive Education (EEI), ensuring an inclusive system with Specialized Educational Service (SES) infrastructure. This article investigates the paradox between the success of this policy in access with increased enrollment and its failure to guarantee infrastructure, focusing on the context of “double vulnerability” of Rural Education. This study is justified by the need to expose how the absence of material conditions prevents the transition from “integration” to “inclusion”, in the terms of Mantoan (2003). The general objective was to diagnose the adequacy of SEA infrastructure and accessibility in rural schools in the state of Bahia. The problem-question is: was the quantitative advance in the enrollment of ISS students in rural schools in Bahia accompanied by qualitative investment in infrastructure, as required by Goal 4? The methodology consisted of a quantitative and qualitative documentary analysis, based on microdata from the 2024 School Census. The results are alarming: in the rural universe of Bahia, only 36% of schools have accessibility and only 21% have Multifunctional Resource Rooms (SRMs). It is concluded that, in this context, Goal 4 was not fully fulfilled, characterizing a precarious integration policy that denies pedagogical support and physical accessibility to the majority of students, directly impacting the teaching praxis.